2022
DOI: 10.1039/d1qi01456k
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed copper phosphide nanocrystals in situ grown in a nitrogen-doped reduced graphene oxide matrix and their superior performance as the anode for lithium-ion batteries

Abstract: A nanocomposite anode material consisting fully of monodispersed copper phosphide (Cu3P) nanocrystals in situ grown into three dimensional (3D) nitrogen-doped reduced graphene oxide (N-RGO) matrixes has been manufactured in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…With these Cu 3 P diffraction peaks and EDX, ICP-OES measurements described above, it can be concluded that the BP has reacted with the copper current collector, forming a new Cu 3 P phase in the BP-Air anode. Extensive studies have shown that Cu 3 P holds a stable electrochemical activity 15 and relatively small volume changes. The presence of the Cu 3 P phase may mitigate the pulverization of BP particles, allowing the active debris particles to remain in contact, as observed in Fig.…”
mentioning
confidence: 99%
“…With these Cu 3 P diffraction peaks and EDX, ICP-OES measurements described above, it can be concluded that the BP has reacted with the copper current collector, forming a new Cu 3 P phase in the BP-Air anode. Extensive studies have shown that Cu 3 P holds a stable electrochemical activity 15 and relatively small volume changes. The presence of the Cu 3 P phase may mitigate the pulverization of BP particles, allowing the active debris particles to remain in contact, as observed in Fig.…”
mentioning
confidence: 99%